PENERAPANACTIVITY BASED COSTING SEBAGAI DASARMENENTUKAN TARIF JASA RAWAT INAP PADARUMAH SAKIT IBU DAN ANAK ARAFAH ANWARMEDIKASUKODONO, SIDOARJO - FIRDAUS, IRWAN (Jurnal Akuntansi AKUNESA, 2016)
Hospitals are establishments engaged in the field to provide health care tothe community. The services provided must meet the standard which the toppriority is the satisfaction of patients. One of the services provided by the hospitalis rates of hospitalization services. With rates of hospitalization services, thisstudy aims to increase knowledge about the application of Activity Based Costingas determining for hospitalization and for comparison also input in the ratecalculation inpatient services at the Maternal and Child Hospital Arafah AnwarMedika Sukodono, Sidoarjo. The method of analysis in this research is using thecase study method. With the case study method will provide an overview of howthe application of hospitalization by using Activity Based Costing and is alreadyin line with the rates of hospitalization services required by the hospital. Keywords: Activty Based Costing, Cost Determination, Hospital